A relay race: intergenerational transmission of housing inequality in urban China. Issue 6 (2nd July 2020) - Cui, Can; Huang, Youqin; Wang, Fenglong
Abstract: Housing affordability has become a critical challenge worldwide, consequently constraining young generation from entering the housing market. Despite growing attention to housing inequality in China, little research has been undertaken to reveal the extent to which a family of origin contributes to housing inequality among young adults. Family resources could support the young generation to achieve homeownership not only directly through intergenerational transfers of wealth, but also indirectly through intergenerational transmission of socioeconomic characteristics. Using the 2013 Fudan Yangtze River Delta Social Transformation Survey, this study constructs a structural equation model to examine the direct and indirect influence of parents' resources on the young generation's housing outcomes. The results show that the direct influence of parents' homeownership is prominent, whereas the impact of transmitted socioeconomic status is limited. Housing advantages of parents, derived from their superior institutional status during China's housing reforms, are being transmitted to their offspring, particularly to sons.